Kajian Yuridis Model Penyelesaian Sengketa Pinjaman Dana Pemulihan Ekonomi Nasional (PEN) oleh Pemerintah Daerah - Winata, I Kadek Ari; Tome, Abdul Hamid (Adagium: Jurnal Ilmiah Hukum, 2025)
This study aims to examine the legal aspects and dispute resolution models in the implementation of the National Economic Recovery (PEN) loan program by local governments. The main questions in this study are: (1) what are the legal provisions governing the PEN loan mechanism by local governments, and (2) how are disputes arising from its implementation resolved? The method used is a normative legal approach with descriptive-analytical analysis of legislation, legal doctrines, and case studies related to the implementation of PEN loans in several regions. Data were collected through literature review and analyzed through deductive legal logic interpretation. The research findings reveal that the implementation of PEN loans is based on various regulations, including Law No. 17 of 2003, Law No. 2 of 2020, Government Regulation No. 43 of 2020, Minister of Finance Regulation No. 105/PMK.07/2020, and Government Regulation No. 56 of 2018. However, in its implementation, various disputes have arisen due to breach of contract, weak supervision, and differences in contract interpretation. Dispute resolution can be pursued through litigation or non-litigation channels, including through the LAPS SJK. This study highlights the importance of strengthening contractual regulations and institutional frameworks for local governments to ensure more accountable management of public loans and minimize the potential for disputes in a systematic and effective manner.